P49 A critical insight into community food aid in a multi-ethnic, multi-faith context. (13th September 2016) - Power, MS
Abstract : Background: According to the BMJ (2013), rising food insecurity in the UK has all the signs of a public health emergency. Yet, research on community support for people experiencing food insecurity is limited. This paper examined community food aid, using data from a city in the north of England (Bradford). The objective was to explore how community food aid meets the needs of a multi-ethnic, multi-faith, low-income population and assess whether the demographic context shapes its activities. Methods: A case-study approach was adopted, including desk-based web research and nineteen interviews involving community organisations with experience of anti-hunger/food security programmes in Bradford. Sample organisations were purposively chosen from 67 identified in the desk-based analysis to form a representative sample. The three-stage analysis approach of Dwyer (2002) was utilised, involving transcript summaries, development of a coding framework based upon common themes in the interviews and a comparison grid of material indexed to themes. Results: Interaction of religious context and food aid 67 food aid organisations were identified. 52% were non-denominational, 36% Christian and 10% Muslim. This is unreflective of Bradford's religious demographic, where 24.7% identify as Muslim and 20.7% describe themselves as having no religion. Ethnic and faith-based exclusivity There was limited ethnic diversity among clients at food aid providers. Emergency food providers served few Pakistani clients and Christian food banks had the least diverse client base. The public expression of faith The expression of faith differed according to the organisation. Among Christian soup kitchens there was some commitment to evangelising, while in Christian foodbanks faith was unforced. None of the Muslim food aid providers interviewed required their clients to engage with Islam. Pragmatism or principle: faith-based motivations Among Christian food aid providers interviewed, faith was an important motivation for provision. In Muslim charities, motivation stemmed primarily from unmet need. However, the extent of religious involvement in community food aid reflected the available resources in religious charities. Conclusion: This is the first academic study in the UK to look at the faith-based arrangements of Christian and Muslim food aid providers. It found limited ethnic diversity among food aid clients, despite the ethnic diversity of the case-study area, however without interviews with food aid users, the reasons for this remain unclear. A further important finding was the apparent exclusionary implications of required engagement by clients with religion at some food aid providers.